'Felson Signs' revisited. Issue 1 (18th February 2013) - George, Phiji Philip; Irodi, Aparna; Nidugala Keshava, Shyamkumar; Lamont, Anthony C
Summary In this article we revisit, with the help of images, those classic signs in chest radiography described by Dr Benjamin Felson himself, or other illustrious radiologists of his time, cited and discussed in 'Chest Roentgenology'. We briefly describe the causes of the signs, their utility and the differential diagnosis to be considered when each sign is seen. Wherever possible, we use CT images to illustrate the basis of some of these classic radiographic signs.